2021
DOI: 10.1126/scitranslmed.abh0272
|View full text |Cite
|
Sign up to set email alerts
|

Deleting DNMT3A in CAR T cells prevents exhaustion and enhances antitumor activity

Abstract: DNMT3A deletion preserves CAR T cell functionality during prolonged stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(114 citation statements)
references
References 83 publications
1
98
0
2
Order By: Relevance
“…Additional modifications include creation of ACT which is resistant to exhaustion [e.g. DNA methyltransferase 3 alpha knock-out ( 95 ) or PD-1 deletion ( 96 )] or tuning ACT to be effective despite low antigen density [e.g. c-Jun overexpression ( 97 , 98 )].…”
Section: Discussion: Overcoming the Immune-suppressive Tme In Act For...mentioning
confidence: 99%
“…Additional modifications include creation of ACT which is resistant to exhaustion [e.g. DNA methyltransferase 3 alpha knock-out ( 95 ) or PD-1 deletion ( 96 )] or tuning ACT to be effective despite low antigen density [e.g. c-Jun overexpression ( 97 , 98 )].…”
Section: Discussion: Overcoming the Immune-suppressive Tme In Act For...mentioning
confidence: 99%
“…A more targeted approach involves deletion of the de novo methyltransferase DNMT3A in CAR T cells, which directly inhibits the acquisition of exhaustion-associated DNA methylation. Indeed, we have shown that DNMT3A KO CAR T cells exhibit enhanced proliferation with sustained antitumor ability as compared to their control counterparts (Prinzing et al, 2021). By characterizing the DNA methylation programs acquired during 10 Cell Reports 37, 110079, November 30, 2021…”
Section: Discussionmentioning
confidence: 99%
“…Building upon our findings from the murine LCMV model system, we recently identified loci targeted by DNMT3A in human CAR T cells undergoing exhaustion in preclinical model systems (Prinzing et al, 2021). Using the DNMT3A targeted genes conserved in both murine and human model systems, we assessed these loci for enrichment of DNA methylation during the post-infusion CAR T cell response.…”
Section: Car T Cell Post-infusion Differentiation Includes Acquisition Of Exhaustion-associated Dna Methylation Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, even after repeated exposure to antigens in vitro , these CAR T cells showed sustained expression of T cell proliferation and memory-related genes, but reduced expression of exhaustion-related genes, resulting in enhanced anti-tumor activity in mouse leukemia and lymphoma models. To achieve sustained blocking of de novo DNA methylation, Prinzing et al ( 71 ) employed CRISPR-Cas9-mediated knockout of Dnmt3a in CAR T cells targeting various tumor-associated antigens and showed that these cells retain proliferative capacity and effector function during repeated antigen stimulation in vitro . The enhanced proliferation of these cells was coupled to decreased methylation of promoter regions of TCF7 and LEF1, TFs that are associated with the stem-like phenotype of T cells, as well as to the increased expression of IL-10.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%